Fibrin glue in managing intractable gingival bleeding in patients with inherited bleeding disorders—a quasi-experimental pilot study - Hussain, Shabneez; Ali Zaidi, Syed Aijaz; Sawani, Sobiya; Moiz, Bushra (Journal of the Pakistan Medical Association, 2024)
This study presents the clinical outcomes of using in-house prepared fibrin glue for controlling gingival bleeding in patients with inherited bleeding disorders (IBD). The objective of the study was to assess the reduction in transfusion days and improvement in compliance for dental evaluation over a one-year period in a low-to-middle-income country. The quasi-experimental pilot study included 40 IBD patients with gingival bleeding. These were divided into two groups: Group A received fibrin glue (n=20), while Group B did not (n=20). The study compared outcome metrics, including the number of treatment days and blood components transfused, using non-parametric tests with a significance threshold of p<0.05. Results showed that Group A required fewer blood components (n=154) as compared to Group B (n=204) (p<0.001). ---Continue